An Analysis of Maxim Flouting in Pokémon: Detective Pikachu Movie - Fendy Aji Setiawan; Havika Haryani (IKIP Siliwangi, 2020)
This study aimed to analyse the use of floating maxim in the Pokémon: Detective Pikachu movie (2019), directed by Rob Letterman. The subject of the research is the conversation between the main character Tim Goodman (Justice Smith) and second character Pikachu (Ryan Reynolds). Pikachu himself is a Pokémon (pocket monster). Barely, a human can talk to a Pokémon, tough they live coexist in a harmony. However, surprisingly the main character of the movie is able to communicate to a Pokémon, though, only Pikachu-the one and only Pokémon he is able to communicate with. The theory used in this research is a theory by Grice about cooperative principle, whereas trough the theory, Grice assumes that a good communication must obey to the rule of the principle. Through the research, there are 8 cases (22.22%) flouting maxim of quantity, 13 cases (36.11%) flouting maxim of quality, 8 cases (22.22%) flouting maxim of relevance and 7 cases (19.44%) flouting maxim of manner. There are four motives found in flouting the maxim, there are competitive motive 16 cases (45.71%). Convivial motive 4 cases (11.42%). Collaborative motive 6 cases (17.14%), and conflictive motive 9 cases (25.71%). Keywords: Maxim, Flouting maxim, Cooperative Principle